2012
DOI: 10.3325/cmj.2012.53.17
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient nuclear DNA typing of the World War II skeletal remains using three new autosomal short tandem repeat amplification kits with the extended European Standard Set of loci

Abstract: AimTo perform an efficiency study of three new amplification kits with the extended European Standard Set (ESS) of loci for autosomal short tandem repeat (STR) typing of skeletal remains excavated from the World War II mass graves in Slovenia.MethodsIn the beginning of the 2011, we analyzed 102 bones and teeth using the PowerPlex ESX 17 System (Promega), AmpFiSTR NGM PCR Amplification Kit (Applied Biosystems), and Investigator ESSplex Kit (Qiagen). We cleaned the bones and teeth, removed surface contamination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The previous studies conducted on WWII samples demonstrated increased possibility for nuclear DNA profiling of partial skeletal remains . Here, we confirmed and proved that combination of autosomal STR and Y‐STR approaches could result with positive identification of several unidentified skeletal remains even in the cases when only one living relative exists.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The previous studies conducted on WWII samples demonstrated increased possibility for nuclear DNA profiling of partial skeletal remains . Here, we confirmed and proved that combination of autosomal STR and Y‐STR approaches could result with positive identification of several unidentified skeletal remains even in the cases when only one living relative exists.…”
Section: Discussionsupporting
confidence: 82%
“…DNA identification of human remains has almost two‐decades‐long history in Bosnia and Herzegovina as well as in the neighboring countries . DNA analysis applied within this study successfully identified and reassembled remains even several decades after they had been buried in the ground and after they were relocated by a powerful landslide.…”
Section: Discussionmentioning
confidence: 97%
“…The latest studies conducted on the WWII samples (4,5,16-19) were done using STR techniques instead of mtDNA, which used to be the mostly used identification method for the samples from that period (20). …”
Section: Discussionmentioning
confidence: 99%
“…The overall matching rates were consistent with Marijanovic (29) although only half of estimated number of missing was accounted for by DNA in our study. Similar to other studies (29,30), several cases required testing with either additional autosomal STRs or Y-chromosome to confirm identify. Palo (31) only analyzed mtDNA, which was used to confirm presumptive identifications based on ID tags.…”
Section: Discussionmentioning
confidence: 82%
“…Molecular genetic methods have been used to identify victims of massacres that took place during and after WW II in Slovenia and Croatia . Also, Finnish soldiers that lost their lives in battles against the former Soviet Union have been identified and repatriated in a similar fashion .…”
Section: Discussionmentioning
confidence: 99%